Digoxin Is Associated With a Decreased Incidence of Angiodysplasia-Related Gastrointestinal Bleeding in Patients With Continuous-Flow Left Ventricular Assist Devices. (August 2018) - Vukelic, Sasa; Vlismas, Peter P.; Patel, Snehal R.; Xue, Xiaonan; Shitole, Sanyog G.; Saeed, Omar; Sims, Daniel B.; Chinnadurai, Thiru; Shin, Julia J.; Forest, Stephen J.; Goldstein, Daniel J.; Jorde, Ulrich P.
Abstract : Background: Gastrointestinal bleeding (GIB) is one of the principal adverse events affecting patients with continuous-flow left ventricular assist devices (CF-LVADs). Despite the early recognition that GIB is commonly because of gastrointestinal angiodysplasia (GIAD), the exact pathophysiology of this process remains elusive. It has been postulated that the abnormal hemodynamic profile in CF-LVAD patients may activate the angiogenesis signaling cascade via the HIF (hypoxia-inducible factor)-1α/angiopoietin-2 pathway leading to formation of GIADs. Digoxin is a potent inhibitor of HIF-1α synthesis, and we hypothesized that its use reduces the incidence of GIAD and GIB in patients with CF-LVAD. Methods and Results: Charts of all adult patients implanted with CF-LVAD between February 2006 and February 2017 were reviewed with particular emphasis on occurrence and cause of GIB. Fifty-four of 199 patients (27%) experienced a GIB. Overall frequency of GIB was lower in the 64 patients receiving digoxin compared with the 135 patients not receiving digoxin (16% versus 33%, P =0.01). Multivariable-adjusted Cox regression analysis confirmed that digoxin use was independently associated with a reduced risk for overall GIB (hazard ratio, 0.49; 95% CI, 0.24–0.98; P =0.045). GIBs were then categorized as non-GIAD, GIAD, or likely GIAD. Although the incidence of non-GIAD was similar in both groups (11% versus 7%, P =0.41), the frequency of GIAD/likely GIAD bleeding was significantly reduced in the digoxin group (5% versus 25%, P =0.0003). Multivariable-adjusted analysis confirmed that digoxin use was independently associated with a reduced risk for GIAD/likely GIAD bleeding (hazard ratio, 0.18; 95% CI, 0.06–0.6; P =0.005). However, digoxin use was not associated with reduced risk for non-GIAD GIB (hazard ratio, 1.54; 95% CI, 0.58–4.08; P =0.39). Conclusions: Use of digoxin was associated with a significant reduction in GIAD-related GIB in patients with CF-LVAD. Abstract : Supplemental Digital Content is available in the text.